The earth as a cradle for life - Stacey, F. D. (Frank D.) (World Scientific, 2013)
This book takes a long-term view of Earth's development as a habitable planet, incorporating physical, chemical and biological processes on the early Earth, through to human perturbations of the modern world and their implications for life in the future.